Norms, Networks, Power and Control: Understanding Informal Payments and Brokerage in Cross-Border Trade in Sierra Leone. Issue 1 (1st January 2021) - van den Boogaard, Vanessa; Prichard, Wilson; Jibao, Samuel
ABSTRACT: Recent research has cast light on the variety of informal payments and practices that govern the day-to-day interactions between traders and customs agents at border posts in low-income countries. Building on this literature, this paper draws on survey and qualitative evidence in an effort to explore which groups are most advantaged and disadvantaged by the largely informal processes and norms governing cross-border trade. We find that variation in strategies and outcomes across traders can only be effectively understood with reference to the importance of norms, networks, power, and the logic of control.